Sonographic Pulmonary Abnormalities in Fetuses With Hypoplastic Left Heart Syndrome and Intact Atrial Septum Undergoing Attempted Atrial Septostomy In Utero. Issue 1 (March 2017) - Mackesy, Meaghan M.; Kalish, Brian T.; Tworetzky, Wayne; Sanders, Stephen; Al-Ibraheemi, Alyaa; Wilkins-Haug, Louise; Lock, James; Marshall, Audrey; Benson, Carol B.
Abstract : Abstract: Fetuses with hypoplastic left heart syndrome (HLHS) and intact atrial septum are a particular subset of HLHS neonates with high perinatal mortality. The reported mortality in these patients is 50% to 70%, even with prenatal diagnosis. Prenatal left atrial and pulmonary venous hypertension results in abnormal pulmonary vascular and parenchymal development. The goal of this study was to compare the sonographic appearance of the lungs in fetuses with HLHS/intact atrial septum to neonatal outcome and/or pathology in cases where in utero intervention was performed to open the atrial septum. We found that lung inhomogeneity on ultrasound corresponded to peripheral lymphatic dilatation at autopsy and was associated with a dismal prognosis even when in utero intervention was successful.